Characteristics of nitrogen and phosphorus loss in runoff from Quercus acutissima Carr. and Robinia pseudoacacia L. under simulated rainfall. Issue 3 (29th May 2020) - Wang, Rongjia; Gao, Peng; Li, Cheng; Dong, Xuede; Zhou, Rui; Gao, Yuemeng; Xu, Jingwei; Dun, Xingjian
Abstract: Subsurface runoff is central to sloping land hydrology research. To explore the mechanism of nitrogen (N) and phosphorus (P) loss in surface and subsurface runoff in mountain forestland, we selected the typical tree species Quercus acutissima Carr. and Robinia pseudoacacia L. as our research objects and carried out simulated rainfall experiments to study the N and P loss characteristics of surface and subsurface runoff on different areas of slope land. Our results show that total N and total phosphorus P concentrations in surface runoff were initially high but tended to be stable as rainfall continued. Surface runoff accounted for most losses of both N and P, with a greater proportion found for forested land than for wasteland. Surface losses of N ranged from 70.8–88.8%, and those of P ranged from 82.2–87.5% of total losses in forest and wasteland, respectively. Our results show that the main pathway for N and P loss was surface runoff. However, N and P loss in subsurface runoff cannot be ignored in research on sloping land hydrology and the control by forestland of nonpoint source pollution in mountain forestland. Our research enriches sloping land hydrology research and provides a basis for the effective control of runoff, N, and P loss in forestland of the mountainous region of China and similar areas around the world.